Exploration of interventions to enhance return-to-work for cancer patients: A scoping review. (December 2021) - Guo, Yu-Jie; Tang, Jue; Li, Jia-Mei; Zhu, Ling-Li; Xu, Jia-Shuo
Objective: With the increasing incidence and earlier onset of cancer, more and more cancer patients are facing the problems of return-to-work. This review is to explore the types, contents, and results of return-to-work interventions for cancer patients. Methods: This scoping review followed Arksey and O'Malley's framework and PRISMA-ScR List. Three Chinese databases and five English databases were searched from the establishment of databases to 31 March, 2021. Article selection and data extraction were conducted by two researchers. Results: Thirty-two studies and 1916 cancer patients with mainly breast and gastrointestinal cancer were included. According to the contents, interventions could be divided into four types: (1) physical interventions ( n = 6), including high-intensity exercise, low-to-moderate intensity exercise, yoga, and upper limb functional training, (2) psychological interventions ( n = 2), including early active individualized psychosocial support and mindfulness-based recovery, (3) vocational interventions ( n = 14), including making work plans, educational leaflets, vocational consultations, electronic health intervention, and interventions targeting at employers, (4) multidisciplinary interventions ( n = 10), including any combination of above interventions. Physical exercises, making working plans, vocational consultations, educational leaflets, two combinations of vocational and physical interventions were validated to have positive results in enhancing cancer patients' return-to-work. Conclusions: Return-to-work interventions for cancer patients are diversified and can be divided into physical, psychological, vocational, and multidisciplinary interventions. Medical staffs can utilize physical exercises, making working plans, vocational consultation, educational leaflets, combinations of vocational and physical interventions to enhance cancer patients' return-to-work. Other interventions still need to be developed and validated.